A non-invasive cardiac output measurement as an alternative to the test bolus technique during CT angiography. Issue 9 (September 2016) - Nijhof, W.H.; Hilbink, M.; Jager, G.J.; Slump, C.H.; Rutten, M.J.C.M.
Abstract : Aim: To investigate the association between a non-invasive cardiac output (CO) measurement and the scan delay, as derived from a test bolus injection protocol. The secondary objective was to determine which factors affect the relationship between the CO and scan delay. Materials and methods: Fifty-five patients referred for a contrast-enhanced (thorax-)abdomen CT examination were included in this feasibility study. A test bolus examination was performed prior to the abdominal CT. During the test bolus injection, the CO of the patient was measured using a non-invasive finger-cuff measurement. Associations were analysed using linear regression analyses. Age, gender, height, weight, and blood pressure were included as potential confounders. Results: Linear regression analysis showed a negative and significant association between CO and delay. The regression formula was as follows: scan delay (seconds) = 26.8–1.6 CO (l/min), with a 95% CI between −2.3 and −1.0 ( p <0.001). Weight appeared to be a confounder in this relation, and gender and blood pressure were effect modifiers. There was no interaction between scan delay and age, height and weight. Conclusions: There is a negative and significant association between the non-invasive CO measurement and the CT scan delay; however, to validate these findings a larger cohort study is needed to investigate whether the non-invasively determined scan delay is as accurate as the use of a test bolus. Highlights: Association between a non-invasive CO measurement and scan delay was investigated. The results show a negative and significant association. Therewith, radiation dose and contrast medium can potentially be reduced.